Is Gigartina a potential source of food protein and functional peptide-based ingredients? Evaluating an industrial, pilot-scale extract by proteomics and bioinformatics - Simon Gregersen Echers; Naim Abdul-Khalek; Rasmus Kranold Mikkelsen; Susan Løvstad Holdt; Charlotte Jacobsen; Egon Bech Hansen; Tobias Hegelund Olsen; Jimmy J.P. Sejberg; Michael Toft Overgaard (Future Foods, 2022)
Seaweeds attract substantial interest as novel sources of sustainable food protein, as they are established sources of industrial hydrocolloids with reasonable protein content. In this study, we investigate the protein composition and nutritional quality of a seaweed protein extract (SPE) from Gigartina sp. The SPE displayed low (<2%), but pH-dependent, aqueous solubility likely due to the harsh conditions employed during extraction. Solubility improved using alkaline buffering and detergent addition to facilitate proteomic characterization by quantitative LC-MS/MS. Proteomics analysis revealed that SPE was dominated by proteins related to light harvest and particularly phycobiliproteins (44%), where phycoerythrin was most abundant (28%). Based on subcellular localization, the extraction method was evaluated as good for release of cellular protein. SPE was rich in essential amino acids (36–41%) and particularly branched chain amino acids (22–24%), and thereby a potential source of nutritional food protein. Using bioinformatic prediction and structural modelling, we found abundant SPE proteins contained novel peptides with the amphiphilic properties required to stabilize an oil/water interface, and thereby high probability of being potent emulsifiers. Based on this study, Gigartina sp. could serve a good candidate for extraction of sustainable, nutritious food protein, with the possibility of further processing into hydrolysates with strong emulsifying properties for use as natural food ingredients.